Deformation and optics based structural design and cost optimization of cylindrical reflector system. (December 2017) - Thalange, Vinayak C.; Dalvi, Vishwanath H.; Mahajani, Sanjay M.; Panse, Sudhir V.; Joshi, Jyeshtharaj B.
Highlights: Structural cost optimization in conjunction with in-house optical ray tracer code. Major focus on reducing system cost for economic feasibility. Important insights from the fabricated design. Important step to reach price parity with coal based power. Abstract: It is a stated goal of renewable energy research to make solar power reach price parity with power from fossil fuel based power plants. Solar-thermal plants are capital intensive and do not benefit strongly from economies of scale. Hence, reducing unit costs is the most effective path to an economically attractive technology. Conventional parabolic trough systems have numerous limitations not least of which are the expensive mirror and support requirements required to maintain high precision in the optics. Further, the flexible hosing necessary to enable a moving receiver leads to excessively high pressure drops and pumping costs. While linear Fresnel systems address much of these shortcomings, they require accurate field alignment of a large number of independent reflecting elements leading to complex maintenance issues. Here we propose a relatively simple design with a small number of reflecting elements with a stationary receiver which is facile to fabricate, transport and install while also be far most cost effective. We also present a structural cost optimization together with optical ray tracer analysis using in-house ray tracer code. The concept has been validated with experiments. The proposed optimum design can be considered as a step toward achieving the economically attractive line concentrator technology.